A taxonomic revision of the myrmecophilous genus Lomechusoides Tottenham, 1939 (Coleoptera: Staphylinidae: Aleocharinae). Part II. The revision of the strumosus species group - Jászay, Tomáš; Hlaváč, Peter; Baňař, Petr (Zootaxa, 2023)
The Lomechusoides strumosus species group is revised and fifteen new species are described: Lomechusoides chekanovskiyi Jászay, Hlaváč & Baňař sp. nov.; L. dlabolai Jászay, Hlaváč & Baňař sp. nov.; L. drobovi Jászay, Hlaváč & Baňař sp. nov.; L. dudkorum Jászay, Hlaváč & Baňař sp. nov.; L. fallax Jászay, Hlaváč & Baňař sp. nov.; L. folgaricus Jászay, Hlaváč & Baňař sp. nov.; L. inflatiformis Jászay, Hlaváč & Baňař sp. nov.; L. poppiusi Jászay, Hlaváč & Baňař sp. nov.; L. primoricus Jászay, Hlaváč & Baňař sp. nov.; L. przewalskyi Jászay, Hlaváč & Baňař sp. nov.; L. reitteri Jászay, Hlaváč & Baňař sp. nov.; L. richteri Jászay, Hlaváč & Baňař sp. nov.; L. rossii Jászay, Hlaváč & Baňař sp. nov.; L. zerchei Jászay, Hlaváč & Baňař sp. nov.; and L. zeyai Jászay, Hlaváč & Baňař sp. nov. Lomechusoides strumosus caucasicus (Wasmann, 1896) is synonymized with L. teres (Eppelsheim, 1884), new synonymy. The synonymy of L. mariae (Palm, 1949) with L. inflatus (Zetterstedt, 1828) is confirmed. Lomechusoides siculus (Fiori, 1914) new status, previously L. strumosus siculus, is elevated to species level. All previously known species: L. inflatus (Zetterstedt, 1828), L. mongolicus (Wasmann, 1897), L. penicillatus Assing, 2015, L. sibiricus (Motschulskyi, 1844), L. siculus (Fiori, 1914), L. strumosus (Fabricius, 1792), L. teres (Eppelsheim, 1884) and L. wellenii (Palm, 1949) are redescribed and illustrated, and a key as well as a catalogue for all species are provided.